PENGARUH KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI DI DINAS KETAHANAN PANGAN DAN PERIKANAN BENGKULU TENGAH - Sisil Nomavi Yure; Ratnawili Ratnawili (Yayasan Insani Mandiri Santani, 2025)
This study aims to examine the influence of communication and organizational culture on employee job satisfaction at the Food Security and Fisheries Agency of Central Bengkulu. This research is a quantitative descriptive study. The population in this research consists of employees of the Food Security and Fisheries Agency of Central Bengkulu. Data collection techniques used include observation and questionnaires. The data were analyzed using descriptive analysis, multiple linear regression analysis, and the coefficient of determination (R²). The results of the study show that communication has a positive and significant effect on employee job satisfaction at the Food Security and Fisheries Agency of Central Bengkulu. This means that the better the communication among employees, the higher their level of job satisfaction. However, organizational culture does not have a significant effect on employee job satisfaction at the agency. A low level of organizational culture implementation corresponds to a lower level of employee job satisfaction. Nevertheless, communication and organizational culture together have a positive and significant effect on employee job satisfaction. This implies that when both communication and organizational culture are strong, employee job satisfaction will increase. Keywords: Communication, Organizational Culture, Employee Job Satisfaction.